Citizenship behaviors included in the social studies article developed for the sixth grade of basic education - Youssef, Asef; Aide, Lena (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of the research is to determine the citizenship behaviors to be met in the social studies subject developed for the sixth grade of the basic education stage, in addition to determining the behaviors of the citizenship involved in it by analyzing the content of this article. The researcher used the analytical descriptive method and designed a list of citizenship behaviors after studying the previous studies in the field of social studies in general and social studies in particular, and reached a list of 42 items representing the behaviors of citizenship. The content of the article was analyzed in light of that list. The following results were obtained: The subjects of social studies for the sixth grade were generally concerned with belonging and allegiance and developing the spirit of allegiance to the country. The behaviors associated with this component came first in terms of inclusion in the course of social studies, while the behaviors related to the rights component came in second place and the duties in third place - Results also indicate the lack of comprehensiveness of citizenship behaviors in all units of study and in some lessons. This may be due to the nature of social studies, which focused on some lessons on natural and historical phenomena, and a clear difference in their distribution in one lesson.